Elimination of multiple reactions of the Phadebact Streptococcus coagglutination test. - Jones, D E (1983)
Strong multiple reactions often occur with the Phadebact Streptococcus test when the culture contains blood. These reactions interfere with the identification of the Lancefield groups of streptococci. Group B streptococci from the vagina of pregnant women are difficult to identify by slide coagglutination because of the frequent presence of blood on culture swabs. Elimination of these multiple reactions caused by blood would permit rapid identification of group B streptococci in pregnant women. Vaginal broth cultures were examined to determine the cause of multiple reactions with slide coagglutination and to eliminate them from the testing procedure. Of 245 maternal broth cultures, 135 (55%) yielded multiple reactions when tested by coagglutination. Such reactions were either eliminated or greatly diminished by heating the broth sample to 90 degrees C for 10 min. It was also found that globulins in the serum may be responsible for multiple reactions with blood. This heating protocol will permit vaginal broth cultures to be rapidly tested for group B streptococci by slide coagglutination.